Slow-release 5-amino-salicylic acid (Pentasa) for the treatment of active Crohn's disease. - Mahida, Y; Jewell, D (1990)
A double-blind, placebo-controlled trial of a slow-release preparation of 5-amino-salicylic acid (Pentasa) has been performed in 40 patients with active Crohn's disease. Over a 6-week period, Pentasa (1.5 g daily) was no different to the dummy tablet in terms of clinical activity (Harvey-Bradshaw Index) or laboratory indicators of inflammation. No serious adverse reactions occurred.